Component formula and preparation method of novel Al-Cr-Fe-V-Ti high-entropy alloy with high wear resistance and corrosion resistance
Through the vacuum arc smelting method of Al-Cr-Fe-V-Ti system high-entropy alloy, the problem that existing materials are difficult to meet high wear and corrosion resistance under extreme operating conditions is solved, and the effects of high hardness, wear and corrosion resistance are achieved. It is suitable for aerospace, chemical industry, marine engineering and other fields.
Patent Information
- Application Number
- CN202510077652.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Existing materials are difficult to meet the performance requirements of high wear and high corrosion resistance in extreme working conditions, limiting the service life and operating stability of equipment and components.
Al-Cr-Fe-V-Ti system high-entropy alloy is used and alloyed by vacuum arc smelting to form an alloy material with high wear resistance, corrosion resistance and high hardness.
The high entropy alloy exhibits high hardness, wear and corrosion resistance, and is suitable for use in extreme working conditions such as high temperature and high pressure and highly corrosive media, extending the service life of equipment and components.
Smart Images

Figure CN119843136A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high entropy alloy materials, and in particular to a composition formula and a preparation method of a novel Al-Cr-Fe-V-Ti series high-entropy alloy with high wear resistance and corrosion resistance. Background Art
[0002] In the rapid development of modern industry and technology, the importance of materials science as the cornerstone supporting technological progress in various industries has become increasingly prominent. Especially in extreme working conditions, such as chemical production, marine engineering, aerospace, machinery manufacturing and other fields, the service equipment has been faced with operating challenges such as extreme high temperature and high pressure environments, highly corrosive media and long-term high wear rates, making the requirements for material performance more stringent. Traditional materials are often difficult to meet the growing performance requirements when faced with complex and changing operating environments. This not only limits the service life and operating stability of key equipment, precision parts and large-scale infrastructure, but also profoundly affects the overall efficiency of industrial production, system safety and sustainability of environmental protection. Therefore, the development of new materials with both high wear resistance and high corrosion resistance is of great significance to promoting industrial upgrading and achieving sustainable development.
[0003] Among them, the unique crystal structure of high entropy alloy brings it many performance advantages over traditional alloys, such as high strength, high hardness, high wear resistance, corrosion resistance, high temperature oxidation resistance, etc. As a new material with excellent comprehensive performance, it has undoubtedly become the key to breakthrough. The emergence of high entropy alloys has broken the limitation of traditional alloys based on one metal element. Multiple elements serve as the matrix of the alloy together, bringing a large number of undeveloped alloy systems. Through the combination of various elements, the addition of trace elements, different molding methods and organizational regulation, alloy materials with the required comprehensive performance can be studied. However, the huge composition space of high entropy alloys has brought great difficulties to alloy design. How to find a new high entropy alloy material with both high wear resistance and corrosion resistance is a major problem that researchers in this field are committed to solving. Summary of the invention
[0004] The purpose of the present invention is to provide a composition formula and preparation method of a novel Al-Cr-Fe-V-Ti series high-entropy alloy with high wear resistance and corrosion resistance, so as to solve the above-mentioned problems in the background technology. The novel Al-Cr-Fe-V-Ti series high-entropy alloy prepared by the present invention exhibits excellent properties of high wear resistance, corrosion resistance and high hardness. These characteristics make it an ideal material choice for extreme working conditions, including extreme high temperature and high pressure environments, highly corrosive media, and long-term high wear rate scenes, and is suitable for use in aerospace, chemical industry, marine engineering and other fields.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide an Al-Cr-Fe-V-Ti high entropy alloy, which comprises the following chemical components in terms of atomic percentage:
[0007] Aluminum 0.01-15%, chromium 5-30%, iron 35-65%, vanadium 5-35% and titanium 5-30%, and the rest are inevitable impurities.
[0008] Preferably, the atomic ratio of Al, Cr, Fe, V and Ti in the Al-Cr-Fe-V-Ti high entropy alloy is 3:14:47:21:15.
[0009] Preferably, the atomic ratio of Al, Cr, Fe, V and Ti in the Al-Cr-Fe-V-Ti high entropy alloy is: 2:16:50:20:12.
[0010] The second technical solution of the present invention is to provide a method for preparing the above-mentioned Al-Cr-Fe-V-Ti high entropy alloy, comprising the following steps:
[0011] The raw materials of various chemical components are mixed and smelted to obtain the Al-Cr-Fe-V-Ti high entropy alloy.
[0012] Preferably, the purity of the raw materials used in the smelting process is ≥ 99.9%.
[0013] Preferably, the smelting atmosphere is a protective atmosphere.
[0014] Preferably, the protective atmosphere is an argon atmosphere.
[0015] Preferably, the melting is vacuum arc melting.
[0016] Preferably, the smelting is performed 6 times.
[0017] Smelting needs to be carried out at least 6 times in order to improve the uniformity of the alloy composition.
[0018] Preferably, the method specifically comprises the following steps:
[0019] (1) Raw material pretreatment: Remove stains and oxide scale on the material surface before weighing, and then ultrasonically clean and dry each metal raw material in anhydrous ethanol. Prepare high-purity metal raw materials of Al, Cr, Fe, V, and Ti according to the composition ratio of the target alloy, and accurately weigh these metal raw materials;
[0020] (2) Vacuum arc melting: The weighed and dried metal materials and the titanium ingots used for oxygen absorption are placed in a vacuum arc melting furnace. To avoid mass loss caused by volatilization of low-melting-point elements and to ensure uniform melting, the accurately weighed metal elements are placed in the pits of the copper mold in order of melting point from low to high, and the alloy is melted under a protective atmosphere;
[0021] (3) Alloy suction casting: The molten alloy liquid is sucked into a copper mold and cooled to form a blank of a predetermined shape to obtain a wear-resistant and corrosion-resistant high-entropy alloy material.
[0022] Preferably, the purity of the raw materials used in smelting the alloy of the present invention is not less than 99.9%.
[0023] Preferably, in step (2) of the present invention, the protective atmosphere during the smelting process is high-purity argon gas, and an arc is struck to burn the titanium ingot before alloy smelting to consume residual oxygen.
[0024] The present invention alloys multiple elements including Al, Cr, Fe, V and Ti by vacuum arc melting to form an alloy material with high wear resistance, corrosion resistance and high hardness.
[0025] The beneficial technical effects of the present invention are as follows:
[0026] The present invention provides a novel Al-Cr-Fe-V-Ti series high-entropy alloy with high wear resistance and corrosion resistance. The Al element in the raw material can promote the formation of a BCC phase, thereby improving the hardness and wear resistance of the material. The added V element forms a strengthening phase in the alloy, which plays a solid solution strengthening effect, so that the prepared alloy can still maintain high strength at high temperatures; and the addition of the V element helps to improve the thermal stability of the alloy, thereby reducing the adverse effects of thermal stress factors on material properties. The Ti element is beneficial to the improvement of the hardness and corrosion resistance of the high entropy alloy. The Cr element can enhance its corrosion resistance and is beneficial to the formation of a Laves phase. The added Fe element is beneficial to the precipitation of the strengthening phase.
[0027] The Al-Cr-Fe-V-Ti high entropy alloy of the present invention has an island-shaped and strip-shaped dual BCC structure, with a Laves phase in the gap. Due to the combination of this unique and complex dual BCC structure phase and the hard Laves precipitation phase, the alloy has a high hardness value. The Ti, Al, V and other elements introduced in the present invention in a suitable proportion can form dense, high-hardness oxide layers such as TiO2, Al2O3, and V2O3, while avoiding the occurrence of high internal stress, thereby further slowing down wear loss and effectively improving wear performance. In terms of corrosion resistance, the introduced Cr, Ti and Al elements are conducive to the formation of highly stable oxides Cr2O3, TiO2 and Al2O3 during the passivation process to inhibit the invasion of corrosive media, and the pitting potential (E pit) is significantly higher than that of traditional materials, indicating that high-entropy alloys have a stronger ability to resist pitting corrosion.
[0028] The new Al-Cr-Fe-V-Ti high entropy alloy prepared by the present invention exhibits excellent properties of high wear resistance, corrosion resistance and high hardness. These properties make it an ideal material choice for extreme working conditions, including extreme high temperature and high pressure environments, highly corrosive media, and long-term high wear rates. It is suitable for use in aerospace, chemical industry, marine engineering and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0030] Figure 1 This is the X-ray diffraction analysis of the product of Example 1-2. The horizontal axis is the 2q angle (°); the vertical axis is the normalized intensity.
[0031] Figure 2 The SEM images of the products of Examples 1-2 are shown in Figures 1-3. (a) and (b) are SEM images of Example 1, and (c) and (d) are SEM images of Example 2.
[0032] Figure 3 EBSD images and BCC phase size distribution images of the products of Examples 1-2. (a) and (b) are EBSD images and BCC phase size distribution images of Example 1, respectively, and (c) and (d) are EBSD images and BCC phase size distribution images of Example 2, respectively.
[0033] Figure 4 The graphs are the friction and wear coefficients of the products of Examples 1-2 under different loads over time, wherein (a) is Example 1 and (b) is Example 2.
[0034] Figure 5 The cross-sectional schematic diagrams of the wear scars of the products of Examples 1-2 under different loads, wherein (a) is Example 1, and (b) is Example 2.
[0035] Figure 6 The SEM images and surface oxygen element distribution diagrams of the products of Examples 1-2 after friction and wear tests. Among them, (a), (b), and (c) are SEM images of the product of Example 1, and (g) is the oxygen element distribution diagram of the product of Example 1; (d), (e), and (f) are SEM images of the product of Example 2, and (h) is the oxygen element distribution diagram of the product of Example 2.
[0036] Figure 7 The surface XPS spectra of the products of Examples 1-2 after friction and wear tests. Among them, (a), (a1), (a2), (a3), (a4), (a5) are from Example 1, and (b), (b1), (b2), (b3), (b4), (b5) are from Example 2.
[0037] Figure 8 This is the potentiodynamic polarization curve of the product of Example 1-2 in 0.6 mol / L NaCl solution.
[0038] Fig. 9 The surface morphology of the product of Example 1-2 after potentiodynamic polarization curve test, wherein (a) and (b) are Example 1, and (c) and (d) are Example 2.
[0039] Fig.10 This is a curve showing the relationship between current density and time of the product of Example 1-2 at a constant potential of 0 V in a 0.6 mol / L NaCl solution.
[0040] Fig.11 The surface XPS spectra of the products of Examples 1-2 after corrosion test. Among them, (a), (a1), (a2), (a3), (a4), (a5), (a6) are from Example 1, and (b), (b1), (b2), (b3), (b4), (b5), (b6) are from Example 2. DETAILED DESCRIPTION
[0041] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0042] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0043] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0045] The metal raw materials used in the embodiment of the present invention are specifically aluminum ingots, chromium ingots, iron ingots, vanadium metal rods and titanium ingots with a purity of ≥99.95%.
[0046] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0047] Example 1
[0048] An Al-Cr-Fe-V-Ti high entropy alloy, consisting of the following chemical components in atomic percentage:
[0049] Aluminum 3%, chromium 14%, iron 47%, vanadium 21% and titanium 15%, together with inevitable impurities.
[0050] The specific preparation method is:
[0051] (1) Select Al, Cr, Fe, V, and Ti metal raw materials, remove surface stains and oxide scale, then ultrasonically clean them in anhydrous ethanol, dry them, and weigh each metal raw material according to atomic percentage;
[0052] (2) The weighed metal materials and the titanium ingot for oxygen absorption are placed in a copper crucible of a vacuum arc melting furnace. To avoid mass loss caused by volatilization of low-melting-point elements and to ensure uniform melting, the metal materials are stacked in the pits of a copper mold in order from low to high melting points, and are melted in an argon atmosphere. After the melting is completed and cooled, the ingot is turned over and melted again. Each ingot is melted 6 times;
[0053] (3) The molten alloy liquid after smelting six times in step (2) is sucked into a copper mold and cooled to obtain an Al-Cr-Fe-V-Ti high entropy alloy (denoted as Al3Cr 14 Fe 47 V 21 Ti 15 ).
[0054] Example 2
[0055] An Al-Cr-Fe-V-Ti high entropy alloy, consisting of the following chemical components in atomic percentage:
[0056] Aluminum 2%, chromium 16%, iron 50%, vanadium 20% and titanium 12%, together with inevitable impurities.
[0057] The specific preparation method is:
[0058] (1) Select Al, Cr, Fe, V, and Ti metal raw materials, remove surface stains and oxide scale, then ultrasonically clean them in anhydrous ethanol, dry them, and then weigh each metal raw material according to atomic percentage;
[0059] (2) The weighed metal materials and the titanium ingot for oxygen absorption are placed in a copper crucible of a vacuum arc melting furnace. To avoid mass loss caused by volatilization of low-melting-point elements and to ensure uniform melting, the metal materials are stacked in the pits of a copper mold in order from low to high melting points, and are melted in an argon atmosphere. After the melting is completed and cooled, the ingot is turned over and melted again. Each ingot is melted 6 times;
[0060] (3) The molten alloy liquid after smelting six times in step (2) is sucked into a copper mold and cooled to obtain an Al-Cr-Fe-V-Ti high entropy alloy (denoted as Al2Cr 16 Fe 50 V 20 Ti 12 ).
[0061] Effect verification
[0062] 1. Perform Vickers hardness test on the product of Example 1-2:
[0063] It has been measured that the high entropy alloy Al3Cr 14 Fe 47 V 21 Ti 15 The hardness value of Al2Cr reaches 794.1±24.26Hv. 16 Fe 50 V 20 Ti 12 The hardness value reaches 700.1±5.76Hv, all of which have high hardness.
[0064] 2. Characterize the crystal structure of the product of Example 1-2:
[0065] Figure 1 This is the X-ray diffraction analysis of the product of Example 1-2.
[0066] Figure 1 In the figure, the horizontal axis is the 2q angle (°); the vertical axis is the normalized intensity.
[0067] Depend on Figure 1 It can be seen that the product of Example 1-2 is a dual-phase alloy system consisting of a BCC phase and a Laves phase.
[0068] 3. Characterize the microstructure of the product of Example 1-2:
[0069] Figure 2The SEM images of the products of Examples 1-2 are shown in Figures 1-3. (a) and (b) are SEM images of Example 1, and (c) and (d) are SEM images of Example 2.
[0070] Figure 3 EBSD images and BCC phase size distribution images of the products of Examples 1-2. (a) and (b) are EBSD images and BCC phase size distribution images of Example 1, respectively, and (c) and (d) are EBSD images and BCC phase size distribution images of Example 2, respectively.
[0071] Depend on Figure 2 It can be seen that the alloy as a whole is composed of large-area island-like structural phases, thin and long strip-like structural phases, and structural phases in the gaps. Figure 2-3 It can be seen from the results that both the island structure phase and the strip structure phase are BCC structures, and the gap is Laves phase.
[0072] Figure 3 As can be seen from (b) and (d), the BCC phase size in the products of Examples 1-2 is non-uniformly distributed, among which the frequency of BCC phase with small size (less than 5 μm) is the highest, with a ratio of approximately 79% and 76%, respectively. This unique and complex combination of dual BCC structure phase and hard Laves precipitation phase creates the possibility of obtaining alloys with high hardness values.
[0073] 4. Conduct wear performance test:
[0074] Figure 4 The graphs are the friction and wear coefficients of the products of Examples 1-2 under different loads over time, wherein (a) is Example 1 and (b) is Example 2.
[0075] Depend on Figure 4 As shown in (a), the wear coefficient curve of Example 1 reaches relative equilibrium after 1000s. The wear coefficient value obtained at this time can be used as an important parameter to measure the friction and wear performance of the material. 14 Fe 47 V 21 Ti 15 The wear coefficient value is 0.26±0.003, which proves that the alloy has a low wear coefficient and excellent wear resistance.
[0076] Depend on Figure 4 As shown in (b), the wear coefficient curve of Example 2 reaches relative equilibrium after 800s. 16 Fe 50 V 20 Ti 12 The wear coefficient is 0.31±0.004, which also has a low wear coefficient.
[0077] Figure 5 The cross-sectional schematic diagrams of the wear scars of the products of Examples 1-2 under different loads, wherein (a) is Example 1, and (b) is Example 2.
[0078] Depend on Figure 5 It can be seen that under different loads, the products of Examples 1-2 all maintain a narrow wear width and a shallow wear depth. The wear rate of the alloy is calculated by the formula, and the optimal wear rates are 1.27×10 -4 mm 3 / N·m and 2.48×10 -4 mm 3 / N·m.
[0079] The calculation formula of wear rate is as follows:
[0080] L = 2Πr;
[0081] V = ΠWDL / 4;
[0082] W r =V / FS;
[0083] Where L (mm) represents the circumference of the wear track during the rotational wear process, r (mm) represents the radius of the wear track; V (mm 3 ) is the volume of the wear track, W (μm) is the width of the wear track, and D (μm) is the depth of the wear track; W r (mm 3 / N·m) represents the wear rate, F(N) is the test load, and S(m) is the total stroke of the wear process.
[0084] 5. After the friction and wear test at a load of 5N, characterization and analysis of the surface after the friction and wear test:
[0085] Figure 6 The SEM images and surface oxygen element distribution diagrams of the products of Examples 1-2 after friction and wear tests. Among them, (a), (b), and (c) are SEM images of the product of Example 1, and (g) is the oxygen element distribution diagram of the product of Example 1; (d), (e), and (f) are SEM images of the product of Example 2, and (h) is the oxygen element distribution diagram of the product of Example 2.
[0086] Figure 6 (a), (b), and (c) show that after wear, Al3Cr 14 Fe 47 V 21 Ti 15 The alloy surface is relatively intact, with shallow grooves and some wear particles and adhesion layers observed. Figure 6As can be seen in (g), an oxide layer is widely generated in the darker contrast part of the SEM image, which hinders further wear damage.
[0087] Figure 6 (d), (e), and (f) show that after wear, Al2Cr 16 Fe 50 V 20 Ti 12 The alloy surface is relatively intact, with shallow grooves, some wear particles and adhesion layers observed, as well as a small amount of tear pits. Figure 6 As can be seen in (h), an oxide layer is widely generated in the darker contrast part of the SEM image, which hinders further wear damage.
[0088] The volume ratio of oxide to the metal consumed to form the oxide (PBR) is an important criterion for judging the integrity of the oxide layer. When the PBR value of the oxide is between 1 and 2, the generated oxide is not easy to crack, has a dense structure and can avoid the existence of high internal stress.
[0089] Figure 7 The surface XPS spectra of the products of Examples 1-2 after friction and wear tests. Among them, (a), (a1), (a2), (a3), (a4), (a5) are from Example 1, and (b), (b1), (b2), (b3), (b4), (b5) are from Example 2.
[0090] Figure 7 (a) shows that the oxides generated on the alloy surface are mainly composed of Al2O3, Cr2O3, Fe3O4, Fe2O3, TiO2, VO2, and V2O3. Oxides such as Al2O3, V2O3, and TiO2 are easy to form a dense, high-hardness oxide layer and avoid high internal stress, so they can effectively hinder wear damage during the wear process.
[0091] Figure 7 (b) shows that the oxides generated on the alloy surface are mainly composed of Al2O3, Cr2O3, Fe3O4, Fe2O3, TiO2, and VO2.
[0092] 6. Corrosion performance test of the product of Example 1-2:
[0093] Figure 8 This is the potentiodynamic polarization curve of the product of Example 1-2 in 0.6 mol / L NaCl solution.
[0094] Figure 8 It is recorded that Al3Cr 14 Fe 47 V 21 Ti 15The corrosion potential is -0.38V, and the pitting potential (E pit ) is 1.12V. During the passivation process, it can form highly stable oxides Cr2O3, TiO2 and Al2O3 to inhibit the invasion of corrosive media, thus showing a high corrosion resistance.
[0095] Al2Cr 16 Fe 50 V 20 Ti 12 The potentiodynamic polarization curve in 0.6 mol / L NaCl solution recorded that its corrosion potential was -0.33 V and pitting potential was 1.04 V.
[0096] Fig. 9 The surface morphology of the product of Example 1-2 after potentiodynamic polarization curve test, wherein (a) and (b) are Example 1, and (c) and (d) are Example 2.
[0097] Fig. 9 It can be seen that the surface of the alloy after corrosion is relatively intact as a whole, with only some small-sized corrosion holes.
[0098] 7. Corrosion characterization of the passivation film formed after corrosion of the product of Example 1-2:
[0099] Fig.10 This is a curve showing the relationship between current density and time of the product of Example 1-2 at a constant potential of 0 V in a 0.6 mol / L NaCl solution.
[0100] Fig.10 In the figure, ACFVT-1 represents Example 1, and ACFVT-2 represents Example 2.
[0101] Fig.10 In the initial stage, the current density of the alloy decreases sharply with time, which represents the rapid formation process of the passivation film; then the current density gradually stabilizes, which indicates that the dissolution and formation of the passivation film on the alloy surface has reached a dynamic balance, and a stable passivation film is generated on the sample surface.
[0102] Fig.11 The surface XPS spectra of the products of Examples 1-2 after corrosion test. Among them, (a), (a1), (a2), (a3), (a4), (a5), (a6) are from Example 1, and (b), (b1), (b2), (b3), (b4), (b5), (b6) are from Example 2.
[0103] Fig.11It is recorded that during the polarization process, the elements in the high entropy alloy form corresponding oxides such as Cr2O3, TiO2, and Al2O3 to form a passivation film, and the relative abundance of these oxides is relatively high. Highly stable oxides form a passivation film with fewer defects, which significantly reduces the possibility of corrosion ion attack and slows down the failure rate of the passivation film, thereby improving the alloy's resistance to pitting corrosion and showing a wider passivation range.
[0104] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An Al-Cr-Fe-V-Ti high entropy alloy, characterized in that: In terms of atomic percentage, it includes the following chemical components: Aluminum 0.01-15%, chromium 5-30%, iron 35-65%, vanadium 5-35% and titanium 5-30%, and the rest are inevitable impurities.
2. The Al-Cr-Fe-V-Ti high entropy alloy according to claim 1, characterized in that: The atomic ratio of Al, Cr, Fe, V and Ti in the Al-Cr-Fe-V-Ti high entropy alloy is 3:14:47:21:
15.
3. The Al-Cr-Fe-V-Ti high entropy alloy according to claim 1, characterized in that: The atomic ratio of Al, Cr, Fe, V and Ti in the Al-Cr-Fe-V-Ti high entropy alloy is 2:16:50:20:
12.
4. A method for preparing the Al-Cr-Fe-V-Ti high entropy alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: The raw materials of various chemical components are mixed and smelted to obtain the Al-Cr-Fe-V-Ti high entropy alloy.
5. The preparation method according to claim 4, characterized in that: The smelting atmosphere is a protective atmosphere.
6. The preparation method according to claim 5, characterized in that: The protective atmosphere is argon atmosphere.
7. The preparation method according to claim 4, characterized in that: The melting is vacuum arc melting.
8. The preparation method according to claim 4, characterized in that: The smelting was performed 6 times.